Nomadic Missiology? Bringing Braidotti's Thought into the Conversation about the Future of Cross-Cultural Mission. (October 2017) - Woods, Paul
Recent discussion about the future of mission has engaged with concepts such as missio Dei, polycentrism, Christendom and glocalisation. In order to provide a philosophical response to these and to introduce a new conversation partner, this article explores key ideas from the nomadic theory of Rosi Braidotti. Notions such as the embodied subject, the rhizome and various forms of becoming could be of benefit to the evolving multilogue about mission futures, and an initial attempt is made to show their relevance to the task of reforming an approach to cross-cultural mission usually associated with Christendom and the power of the West.